2019
DOI: 10.1177/2158244019835936
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Cancer Genetic Panel Testing: A Review of the Literature

Abstract: Cancer genetic testing (CGT) is a powerful diagnostic test that improves cancer prevention and early detection among individuals at high genetic risk of cancer. Since the completion of the mapping of the Human Genome Project, CGT has become increasingly available in the clinical setting. However, as gene discovery and sequencing technology improve, the impact of these advancements on patients is less understood. The use of multigene cancer gene panel tests has become increasingly prevalent; as such, the likeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Each of the above-mentioned issues should be brought to the individual's attention and hence they formulate the underpinnings of informed consent. Signing a consent form should be preceded by disclosing full information on the possibilities and limitations of a given genetic test, the consequences of diagnosing a cancer predisposition syndrome and its management [8,16,17,22,23].…”
Section: Discussion On Genetic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the above-mentioned issues should be brought to the individual's attention and hence they formulate the underpinnings of informed consent. Signing a consent form should be preceded by disclosing full information on the possibilities and limitations of a given genetic test, the consequences of diagnosing a cancer predisposition syndrome and its management [8,16,17,22,23].…”
Section: Discussion On Genetic Testingmentioning
confidence: 99%
“…In instances when the condition might be related to mutations in many different genes, multigene panels have been introduced. There are no uniform recommendations on the number of genes that should be included in such a panel, and there are ongoing discussions on the relevance of particular genes to some cancers [18,22,23].…”
Section: Genetic Testsmentioning
confidence: 99%
“…Further studies are indicated to evaluate patients meeting criteria compared with those who do not, as well as pathogenic variants identified outside of the expected spectrum. Additionally, concern should be given to the mental distress that genetic testing may put on an individual, especially when little to no information is available on newer or nonactionable genes ( Harris & Hutson, 2019 ). Testing decisions should be individualized based on personal history, family history, and psychological mentality.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, three types of smartphone‐based optical imaging biosensors are discussed according to the detection technique: smartphone‐based colorimetric biosensor, 14 smartphone‐based fluorescence biosensor, 15 and smartphone‐based microscopic imaging biosensor (see Figure 1). The targets of these detection techniques include the different disease biomarkers of infectious diseases, 16 hereditary diseases, 17 and cancers 18 . It must be noted that these three types do not fully cover all the existing types of smartphone‐based biosensors, other types of smartphone‐based biosensors such as electrochemical sensors and multimode‐sensing sensors are also applied to the field of genetic testing; however, the review mainly considers the common optical biosensing applications of these three types as per the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…Summary of the representative achievements of smartphone‐based optical imaging biosensor in three different applications. The applications cover detections of infectious diseases, hereditary diseases, and cancers 16–18 . Reproduced with permission from Ref.…”
Section: Introductionmentioning
confidence: 99%